Principles of plant health and quarantine - Ebbels, D. L. (CABI Pub., 2003)
This book is an introductory text on the principles of plant health and quarantine and is aimed at plant health administrators and inspectors as well as students and scientists. Topics covered include the history of plant health controls, current international phytosanitary regimes, notes on import and export controls, eradication and containment, certification and marketing schemes, indexing and diagnosis in plant health, pest risk analysis and hygiene and precautionary measures. The book also includes a glossary and a list of related web sites. It will be of interest to those working in plant science, plant pathology and plant entomology.